Modernization of operational and analytical indicators of functional and technological reliability of development construction projects - Zhaldak, R.; Druzhynin, M. (Ways to Improve Construction Efficiency, 2023)
The article discusses the background and main aspects need to update modern paradigm of construction organizational and technological planning, it changes according to the current understanding of providing comprehensive reliability construction projects realization as flow multiplier set of key indicators of a project. Considered flaws of one of the most common methodology in prior definition of organizational and technological reliability of the construction project, which belongs to the single-purpose optimization problems and concerns predicting the probability of an execution process with given parameters. Modernization of operational and analytical indicators of functional and technological reliability of development construction project executors is a key aspect of improving construction processes and ensuring the quality of work. This abstract explores modern strategies and methods aimed at improving the efficiency and reliability of construction projects. Tools and approaches to measuring functional and technological reliability are analyzed, including the use of metrics for problem response time, problem solving efficiency, and overall performance. Models and methods for predicting risks associated with the technical aspects of construction and operation of facilities are considered. Particular attention is paid to the development of integrated approaches to monitoring and data analysis that allow for the prompt identification of potential problems and avoidance of negative consequences. Examples of the introduction of modern technologies, such as artificial intelligence, data analytics and the Internet of Things, into construction control systems are provided. The advantages of these innovative approaches in ensuring the quality and timeliness of construction works, as well as reducing the risks of functional disruptions are highlighted. The analysis of these approaches allows us to determine the optimal strategies for modernizing operational and analytical indicators of functional and technological reliability in development construction projects.